Web-based therapy for hemianopic alexia is syndrome-specific. Issue 3 (25th May 2015) - Woodhead, Zoe V J; Ong, Yean-Hoon; Leff, Alex P
Abstract : Rehabilitation studies rarely test the specificity of an intervention by using a control group who are matched to the therapy group in terms of baseline impairment, but who do not have the same causative syndrome. In this study, we tested the specificity of an eye movement therapy for a common, acquired reading disorder called hemianopic alexia, by comparing hemianopic participants with slow text reading, to age and reading speed matched controls without hemianopia. The study was carried out using an online therapy programme called 'Read-Right' that contains validated tests of the visual field and text reading speed, as well as an eye movement therapy: laterally scrolling text. 201 self-selected participants completed at least 5 h of online therapy. After excluding those with reading speeds incompatible with hemianopic alexia and those with bilateral abnormalities on their visual field test, we were left with 105 who were then classified into one of three groups depending on their visual field: (1) right-sided hemianopia (n=47); (2) left-sided hemianopia (n=36); (3) no hemianopia (n=22, control group). The three groups did not differ in terms of baseline text reading speed, but they were all significantly slower than expected based on normative data from the same age range. A repeated-measures analysis of variance showed a significant therapy by group interaction (p=0.039). Post hoc, paired t tests revealed that this was driven by reading speed improvements for the right-sided and left-sided hemianopic alexic groups but not the controls. This result demonstrates that a clinically validated therapy for hemianopic alexia improves text reading speed in hemianopic patients but not in participants matched for slow text reading but without hemianopia. This adds weight to the hypothesis that eye movement therapies are syndrome-specific. It also demonstrates an advantage of using web-based vehicles to deliver syndrome-specific therapies that can be accessed by patients worldwide.